The vendetta defense - Scottoline, Lisa. (New York : HarperCollins, 2001)
Lawyer Judy Carrier agrees to defend an old Italian pigeon -keeper accused of murder, but the complexities of the case, which centers on a fifty-year-old vendetta, leave her in doubt of her ability to mount a convincing defense.
Keywords: Italian Americans -- Fiction; Trials (Murder) -- Fiction; Homing pigeons -- Fiction; Women lawyers -- Fiction; Vendetta -- Fiction; Philadelphia (Pa.) -- Fiction; Legal stories -- 2001.; Mystery fiction